150 ESTABLISHING A PFO PATHWAY FOR ACUTE STROKE PATIENTS WITH A POSITIVE BUBBLE STUDY. (25th October 2022) - Donaghy, L; Saiva, L; Guilfoyle, P; Sheehan, O; Dolan, E
Abstract: Background: A bubble study is performed routinely on patients under the age of 65 years of age with a confirmed diagnosis of either acute ischaemic stroke or TIA in order to assist with the presence of a Patent Foramen Ovale(PFO)/Atrial Septal Defect(ASD) as an aetiology for the stroke event. Historically, a referral letter would be written to a hospital who specialises in cardiac structural surgeries, requesting a review of a patient with a positive bubble study and acute stroke. Closure would typically exceed 9 months. Methods: The Stroke RANP led out on the project as she performs all bubble studies in stroke survivors. A designated Cardiologist, who also works in a hospital where PFO closures takes place, is notified by the RANP or team about a positive bubble study and the images are reviewed. It is then decided if the patients requires a TOE or not. A 2-page PFO referral form was created which contains all relevant information. Results: Stroke RANP performed 92 bubble studies between January 2021 and May 2022. There were 18 positive studies (20% positivity rate): 7 positive studies from January to August 2021 (pre-pathway) and 11 positive studies from September 2021 to May 2022 (post-pathway). 72% (5/7) of patients had a TOE performed following a positive bubble study result pre-pathway, whereas only 1 TOE was performed out of 11 cases (9%) post-pathway. The time from positive bubble study to closure time reduced from 9months on average to 3 months. Conclusion: There was a 63% reduction in the number of TOEs being performed for patients with a positive bubble study with the introduction of this PFO pathway. Additionally, there was a 6-month reduction time from the positive bubble study result to closure. This pathway has improved patient outcomes for this young group of stroke survivors and assists with the reduction of further stroke events in the future.